PENGARUH KARAKTER INDIVIDU DAN LINGKUNGAN PEMBELAJARAN TERHADAP PENINGKATAN KARIR - Pamela Magdalena (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
This research tries to analyze how individual character and learning environment, in the form of advanced study of the knowledge of diploma program owned into the knowledge of one strata of Management, have an effect on career owned by employees. The research was conducted in one of Jakarta’s top business univercity. The results showed that individual characters have a significant effect on career improvement. This is evidenced also by the statement of employees who become respondents that the purpose of continuing studies such as to develop a career, in addition to job demands, and as a means of adding knowledge. In addition, the learning environment has a significant effect on individual character and on career